Water safe Worcester: student-led drowning prevention in an adolescent underserved population - Playter, Katharine; Hurley, Erin; Lavin-Parsons, Kendall; Parida, Kurren; Ballinger, Zachary; Wong, Kaitlyn; Valente, Alycia (Frontiers in Public Health, 2024)
Adolescents aged 15 to 19 years have the second highest fatal drowning rate of any age group, second only to toddlers aged 12 to 36 months. This risk is amplified in black, indigenous, and people of color (BIPOC), and those of low socioeconomic status. Worcester, MA is a diverse city with over 40% of residents identifying as BIPOC and 20% living below the poverty line. The city has multiple natural bodies of water available for recreation, putting Worcester residents, particularly adolescents, at high risk of drowning. It is known that swimming lessons provided to adolescents significantly improve their swimming skills, however many programs are tailored to young children and are not appropriate for adolescents. Students from the University of Massachusetts T.H. Chan Medical School (UMass Chan), in collaboration with community partners, developed a water safety and swim education program tailored to Worcester adolescents as a means for an age-appropriate swim experience and education, community engagement, and injury prevention.Water Safe Worcester (WSW) was established as a city-wide injury prevention program that included swim lessons offered by medical students at the Central Community Branch YMCA in Worcester, MA. Instructors included UMass Chan medical students, graduate students, and staff. Adolescent YMCA members were invited to participate in lessons free of charge. Lessons were 90 minutes and emphasized a three-fold approach: (1) expand knowledge of water safety and what to do in an emergency, (2) increase swimming skills, and (3) reduce fear of water. The overall attendance for the 2023 spring and summer sessions offered was 73 students, including multiple swimmers who attended more than one session. A total of 12 volunteers participated, which included 9 first-year medical students, one PhD student, one research assistant, and one surgery resident from UMass Chan. WSW demonstrated promising outcomes during its swim education classes, suggesting that WSW is a successful model to promote water safety, reduce the risk of drowning, and expand access to life-saving skills to Worcester's at-risk adolescents. This program serves as a critical step toward health equity while also providing an avenue for public health and injury prevention exposure for medical students.